2020
DOI: 10.1101/2020.12.18.423406
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Origin and evolution of the cannabinoid oxidocyclase gene family

Abstract: Cannabis is an ancient crop representing a rapidly increasing legal market, especially for medicinal purposes. Medicinal and psychoactive effects of Cannabis rely on specific terpenophenolic ligands named cannabinoids. Recent whole-genome sequencing efforts have uncovered variation in multiple genes encoding the final steps in cannabinoid biosynthesis. However, the origin, evolution, and phylogenetic relationships of these cannabinoid oxidocyclase genes remain unclear. To elucidate these aspects we performed c… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 86 publications
2
9
0
Order By: Relevance
“…Whether (and if) the expression of these sequences correlates with the ability of the different varieties to produce CBCA in some stage of their development and consequently if they should all be considered as actually involved in CBCA biosynthesis in planta, is still to be determined. This is true not only for the sequences identified in this work, but also for all other putative CBCAS sequences released so far [7].…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…Whether (and if) the expression of these sequences correlates with the ability of the different varieties to produce CBCA in some stage of their development and consequently if they should all be considered as actually involved in CBCA biosynthesis in planta, is still to be determined. This is true not only for the sequences identified in this work, but also for all other putative CBCAS sequences released so far [7].…”
Section: Discussionsupporting
confidence: 61%
“…The genetics of cannabinoid synthesis has been studied for several years and different genes encoding these enzymes are known, each made of a single exon, with THCAS and CBCAS sharing 92% identity at amino acid level and 84% and 83% identity compared to CBDAS, respectively [3][4][5][6][7]. While THCAS and CBDAS have been widely studied at genetic and molecular level, little information is available on CBCAS genes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interesting areas of future study will be to correlate chemotype and genotype directly and determine why other minor cannabinoids have such low abundance in commercial Cannabis . For example, there are numerous CBC-related genes (van Velzen and Schranz 2020) but we observe very low levels of CBC (Figures 1-2), supporting previous claims that CBCA synthase may not be selective for CBC production (Vergara et al 2020).…”
Section: Discussionsupporting
confidence: 89%
“…These likely arise from distinct genotypes. The genes giving rise to the cannabinoid synthases responsible for producing the major cannabinoid acids are highly similar (Vergara et al 2019; van Velzen and Schranz 2020; Vergara et al 2021b). Copy number variation (Vergara et al 2019; Vergara et al 2021b) or allelic variation (Onofri et al 2015) in the genes encoding these enzymes may explain the observed variation in cannabinoid ratios.…”
Section: Discussionmentioning
confidence: 99%